2012
DOI: 10.1017/s0263034612000444
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic self-focusing of super-Gaussian laser beam in plasma with transverse magneticfield

Abstract: This paper presents an investigation of a self-consistent, theoretical model, which explains the ring formation in a superGaussian laser beam propagating in plasma with transverse magnetic field, characterized by relativistic nonlinearity. Higher order terms (up to r 4 ) in the expansion of the dielectric function and the eikonal have been taken into account. The condition for the formation of a dark and bright ring has been used to study focusing/defocusing of the beam. It is seen that inclusion of higher ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…On the other hand, the ponderomotive nonlinearity produces plasma density perturbation thereby affecting the focusing properties of the laser pulse. The plasma electrons are set into quiver motion by the intense laser beam leading to ponderomotive nonlinearity which produces electron density perturbation in the plasma [10][11][12][13][14][15]. Since both the ponderomotive as well as the relativistic nonlinearities affect the propagation of the laser beam through partially stripped plasma, they have been studied in detail by earlier workers for classical case theoretically [16][17][18] and experimentally [19][20][21] and reviewed elegantly [14,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the ponderomotive nonlinearity produces plasma density perturbation thereby affecting the focusing properties of the laser pulse. The plasma electrons are set into quiver motion by the intense laser beam leading to ponderomotive nonlinearity which produces electron density perturbation in the plasma [10][11][12][13][14][15]. Since both the ponderomotive as well as the relativistic nonlinearities affect the propagation of the laser beam through partially stripped plasma, they have been studied in detail by earlier workers for classical case theoretically [16][17][18] and experimentally [19][20][21] and reviewed elegantly [14,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…[19−20] Few studies of self-focusing have been reported on elliptical Gaussian beam, [21−23] cosh Gaussian beams, [24] Hermite Gaussian beams, [25] Hermite-Cosh-Gaussian beams [26] and super Gaussian beams. [27] From our studies, we have observed that, presently, there is an increase in interest in exploring a new technique of combining multiple beams to achieve high power densities at the target. [28−31] However combining identical four beams is mathematically simpler than combining two beams.…”
Section: Introductionmentioning
confidence: 99%
“…[6−10] The self-focusing decreases with increase in intensity of the beam due to dominance of diffraction effect at high intensity. [11] Gill et al [12] used the higher order paraxial theory to study the relativistic self-focusing of super Gaussian laser beam in plasma and reported that the inclusion of higher order terms of dielectric function affects the behavior of beam width parameter significantly and the magnetic field improves the self-focusing of laser beam in plasma. [13−14] Recently, Habibi and Ghamari [15] have extended the same theory for the focusing of a cosh-Gaussian laser beam in quantum plasma.…”
Section: Introductionmentioning
confidence: 99%